2019
DOI: 10.1016/j.pt.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Tick–Pathogen Interactions: The Metabolic Perspective

Abstract: The first tick genome published in 2016 provided an invaluable tool for studying the molecular basis of tick-pathogen interactions. Metabolism is a key element in host-pathogen interactions. However, our knowledge of tick-pathogen metabolic interactions is very limited. Recently, a systems biology approach, using omics datasets, has revealed that tick-borne pathogen infection induces transcriptional reprograming affecting several metabolic pathways in ticks, facilitating infection, multiplication, and transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 68 publications
0
23
0
Order By: Relevance
“…The fact that ticks and not G. mellonella are tolerant to C. burnetii may highlight pivotal biological differences between these arthropods. Indeed, recent observations showed that intracellular tick-borne pathogens modulate tick physiology and tick cell processes, including immunity and apoptosis, leading to tolerance of intracellular infections [41]. A similar modulation of O. moubata metabolism by C. burnetii may thus take place, not impacting tick survival and subsequently enhancing their vector competence.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that ticks and not G. mellonella are tolerant to C. burnetii may highlight pivotal biological differences between these arthropods. Indeed, recent observations showed that intracellular tick-borne pathogens modulate tick physiology and tick cell processes, including immunity and apoptosis, leading to tolerance of intracellular infections [41]. A similar modulation of O. moubata metabolism by C. burnetii may thus take place, not impacting tick survival and subsequently enhancing their vector competence.…”
Section: Discussionmentioning
confidence: 99%
“…Using gas chromatography coupled to a mass spectrometry-based approach, a recent study explored the differences between the metabolic profiles of B. burgdorferi-infected and naïve I. scapularis nymphal ticks during blood meal engorgement (Hoxmeier et al, 2017). Additional studies on tick-pathogen metabolic interactions (see review (Cabezas-Cruz et al, 2019)) are certainly warranted, as they will contribute both to our understanding of the complex interactions between B. burgdorferi and Ixodes ticks, and to the development of novel interventions against tick-borne infections.…”
Section: Ixodes Proteomics and Metabolomicsmentioning
confidence: 99%
“…In addition, results demonstrate that in infection condition, R. sanguineus metabolism is directed differently in each lineage. According to Cabezas-Cruz et al (2019), the response of tick cells to the pathogens is associated with tolerance to infection and, the modulation of tick metabolism by tick-borne pathogens, is a result of coevolution and adaptation, indicating that both R. sanguineus lineages had a different co-evolution with E. canis. There are many proteins involved in metabolic processes, however, the approach used in this study (comparison between the two different lineages) do not allow to predict how the pathogen exploit these molecules.…”
Section: Rhipicephalus Sanguineus Tropical Lineage Is More Tolerant To Ehrlichia Canis Infectionmentioning
confidence: 99%